Effect of Reactive Balance Training Involving Repeated Slips and Trips on Balance Recovery Among Older Adults: A Blinded Randomized Controlled Trial. (5th February 2019) - Okubo, Yoshiro; Sturnieks, Daina L; Brodie, Matthew A; Duran, Lionne; Lord, Stephen R
Abstract: Background: This study examined whether reactive balance training (exposures to slips and trips) could improve balance recovery and reduce perturbation-induced falls among older adults. Methods: Forty-four community-dwelling older adults participated in a parallel, blinded randomized controlled trial conducted in a research institute in Sydney, Australia in 2017–2018 (ACTRN12617000564358). The intervention group ( n = 22) underwent three 40 minutes sessions (total 120 minutes) that exposed them to (1) 20 trips, (2) 20 slips, and (3) 10 trips and 10 slips in mixed order, over 2 days. The control group ( n = 22) received one 40 minutes session of sham training. The primary outcome was falls (>30% body weight in harness) when exposed to trips and slips at post-assessment. Results: At post-assessment, a total of 51 falls (23 and 27 falls from induced slips and trips, respectively) were recorded in the laboratory. Relative to the control group, the intervention group experienced fewer total falls (rate ratio [RR] = 0.40, 95% confidence interval [CI] = 0.22–0.76), slip falls (RR = 0.33, 95% CI = 0.12–0.90) and trip falls (RR = 0.49, 95% CI = 0.21–1.12). Eight participants reported adverse events (5 in the intervention group and 3 in the control group) which were related mainly to discomfort caused by a suboptimal harness used in the initial stages of the trial. Conclusions: The reactive balance training reduced perturbation-induced falls by 60% indicating improved balance recovery from trips and slips. A comfortable safety harness system is essential to prevent discomfort. Reactive balance training may complement traditional exercise programs in fall prevention interventions.